The effects of Heat Treatment (T6) Technique and Some Centrifugal Casting Parameters on the Fatigue behavior of the Composite Material (A380/Al2O3) - Salah F. AbdulJabbar; Thaer F.A. ALSultan; Faris H.; Mohand A. Hamid (Tikrit Journal of Engineering Sciences, 2017)
Aluminum alloys composite is one of the most common types of composite materials and are used a lot in the recent years. In this paper, it had been dealt with the effects of the heat treatment techniques and some centrifugal casting parameters on the fatigue behavior of the composite material (A380/Al2O3) for high-cycle fatigue resistance which is one of the most important property for the automotive industry. It has been used aluminum alloy A380 with alumina particles Al2O3 to form composite materials through the process of centrifugal casting. The proportions were 10% and 20% with a grain size 63μm. After there, it has been manufactured Thirty-two models of composite material (A380/ Al2O3). Half of them are examined directly without treatment while the other half was treated with (T6) and then examined. The results showed that adding the amount of alumina 20% without heat treatment will increase relatively resistant composite material for the fatigue resistance by 17% percentage. And adding 10% alumina to the composite material and them cause distortion of the surface structure samples had been by blisters with completely discolored. A high Alumina content improves the fatigue behavior of the composite material (A380/Al2O3).   DOI: http://dx.doi.org/10.25130/tjes.24.2017.29